Neurotensin and Xenin Show Positive Correlations With Perceived Stress, Anxiety, Depressiveness and Eating Disorder Symptoms in Female Obese Patients - Wölk, Ellen; Stengel, Andreas; Schaper, Selina Johanna; Rose, Matthias; Hofmann, Tobias (Frontiers in Behavioral Neuroscience, 2021)
Objective: Neurotensin and xenin are two closely related anorexigenic neuropeptides synthesized in the small intestine that exert diverse peripheral and central functions. Both act via the neurotensin-1 receptor. In animal models of obesity reduced central concentrations of these peptides have been found. Dysregulations of the acute and chronic stress response are associated with development and maintenance of obesity. Until now, associations of both peptides with stress, anxiety, depressiveness and eating disorder symptoms have not been investigated. The aim of the present study was to examine associations of neurotensin and xenin with these psychological characteristics under conditions of obesity. Methods: From 2010 to 2016 we consecutively enrolled 160 inpatients (63 men, 97 women), admitted due to obesity and its mental and somatic comorbidities. Blood withdrawal und psychometric tests (PSQ-20, GAD-7, PHQ-9 and EDI-2) occurred within one week after admission. We measured levels of neurotensin and xenin in plasma by ELISA. Results: Mean body mass index was 47.2±9.5 kg/m2. Concentrations of neurotensin and xenin positively correlated with each other (women: r=0.788, p<0.001; men: r=0.731, p<0.001) and did not significantly differ between sexes (p>0.05). Women generally displayed higher psychometric values than men (PSQ-20: 58.2±21.7 vs. 47.0±20.8, p=0.002; GAD-7: 9.7±5.8 vs. 7.1±5.3, p=0.004; PHQ-9: 11.6±6.6 vs. 8.8±5.9, p=0.008; EDI-2: 50.5±12.8 vs. 39.7±11.9, p<0.001). Only women showed positive correlations of both neuropeptides with stress (neurotensin: r=0.231, p=0.023; xenin: r=0.254, p = 0.013), anxiety (neurotensin: r=0.265, p=0.009; xenin: r=0.257, p=0.012), depressiveness (neurotensin: r=0.281, p=0.006; xenin: r=0.241, p=0.019) and eating disorder symptoms (neurotensin: r=0.276, p=0.007; xenin: r=0.26, p=0.011); whereas men did not (p>0.05). Conclusions: Neurotensin and xenin plasma levels of female obese patients are positively correlated with perceived stress, anxiety, depressiveness and eating disorder symptoms. These associations could be influenced by higher prevalence of mental disorders in women and by sex hormones. In men, no correlations were observed, which points towards a sex-dependent regulation.